Analysis of the Impact of Acquisition on Firm Financial Performance - Nurjanah, Latri; Fijrijanti, Tettet (Research of Finance and Banking, 2023)
This study aims to prove that firms carry out an acquisition strategy intending to obtain additional funds to achieve better firm synergy and encourage increased firm performance. This study uses a comparative research method. The research sample comprised 18 manufacturing firms that made acquisitions between 2008 and 2020. The analytical tools used were the paired sample t-test and the Wilcoxon signed rating test. The research results show that return on equity (ROE)manufacturing firms have a significant difference before and after the acquisition. Moreover, there is no significant difference in the current ratio, asset turnover ratio, debt to equity ratio, and price book value ratio of manufacturing firms before and after the acquisition. In contrast, the ratio of return on equity of manufacturing firms has a significant difference between before and after the acquisition. This study's results indicate that the acquisitions made by firms do not make a significant difference to manufacturing firms